A Guiding Framework for Nutrition Public Expenditure Reviews - Wang, Huihui (World Bank, Washington, DC, 2022)
The main purpose of this Guiding Framework document is to present the key elements of a Nutrition Public Expenditure Review (NPER) and offer guidance, practical steps, and examples on carrying out an NPER. It targets a wide-ranging audience, including country nutrition policy makers, development partners (DPs), government technical staff, and advocates and practitioners who are tasked with carrying out NPERs (who are also the main target audience). The Guiding Framework draws upon good practices from the growing body of NPERs as well as common practices and expertise from Public Expenditure Reviews (PERs). However, given the limited number of existing NPERs, this document should be considered as a starting point, or a ‘living document,’ and is not meant to provide a comprehensive coverage of a standard methodology for NPERs, as this would require further work and analysis. Specifically, this Guiding Framework aims to be a useful tool for practitioners involved in developing an NPER. It does this by: (i) situating NPERs within the context of other similar efforts such as a nutrition budget analysis or sector-specific PERs; (ii) presenting the literature of existing NPERs and related literature to serve as reference; (iii) providing guidance on preparatory work before beginning an NPER (i.e., defining the scope, setting up an NPER team, and identifying data sources); (iv) providing guidance on conducting the core analysis (i.e.,framing the analysis, analyzing the institutional framework, and linking the analysis to the policy dialogue); and (v) clearly identifying knowledge gaps and necessary additional work to enhance the robustness of future NPER analysis.